Esthetic and Functional Restorative Management with Composite Resin Veneers in a Patient with Bruxism: A Case Report - , Mariana Veras Godeiro; , José Evando da Silva-Filho; , Ana Beatriz Cardoso-Oliveira; , Ana Paula Caracas-de-Araújo; , Eduardo Diogo Gurgel-Filho; , Maria Denise Rodrigues de Moraes (Archives of Current Research International, 2025)
A 40-year-old male patient presented with multiple fractures and failures in direct composite restorations on his maxillary anterior teeth, associated with nocturnal bruxism. He sought care at the clinical training facility of the Professional Master’s Program in Dentistry at the University of Fortaleza. Clinical examination, patient interview, and photographic documentation confirmed esthetic compromise and functional instability due to failed restorations. These were removed and replaced with direct composite resin veneers, following strict adhesive, insertion, polymerization, and polishing protocols. To manage the underlying parafunctional habit, a 2 mm-thick acrylic stabilizing occlusal splint was fabricated and delivered, along with occlusal adjustments on the teeth, restorations, and splint. In this case, nocturnal bruxism was considered the primary contributing factor to the repeated restorative failure, emphasizing the need for a multidisciplinary approach. Based on the treatment strategy applied and its outcomes, a clinical management suggestion is presented to support conservative esthetic and functional rehabilitation in similar cases.